Pengaruh Penggunaan Aplikasi Artificial Intelligence Terhadap Minat Belajar Mahasiswa Teknik Elektro - Riani, Elsa Cipto; Effendi, Hansi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Interest in learning is a high inclination towards something, supported by passion and desire, and becomes a motivation to carry out certain behaviors, including in the context of learning. The use of Artificial Intelligence (AI) applications to assist with lectures and completing course assignments is becoming an increasingly popular phenomenon among students. By using AI applications, students get fast and efficient data access to learning resources, resulting in more accurate results and saving the time needed to complete assignments. This research aims to find out whether there is an influence from the use of AI applications on the learning interest of Electrical Engineering students. This research is descriptive research with quantitative methods. The population of this study were all active electrical engineering students at Padang State University. while the samples were taken using the Solvin formula. The research process was carried out by distributing questionnaires via Google Forms. The results of this research show that there is a significant influence between the use of AI applications on electrical engineering students' interest in learning and the direction of the influence is positive.